Herniation of the stomach and colon into the right hemithorax following a transthoracic Collis-Belsey operation - BATIREL, HASAN FEVZİ (EKIN TIBBI YAYINCILIK LTD STI-EKIN MEDICAL PUBL, 2011)
Collis gastroplasty and Belsey fundoplication is a good choice for patients with a large hiatal hernia and associated reflux. In this article, we report a patient who presented as post-emetic with herniation of the stomach and colon into the right hemithorax, within two months after the Collis Belsey procedure. The patient was reoperated on, and the hernia was reduced through a left posterolateral thoracotomy. At the 22-month follow-up, the patient was well and was able to tolerate a full diet without any symptoms.
Keywords: Collis-Belsey operation; gastroesophageal reflux; intrathoracic hernia; LAPAROSCOPIC ANTIREFLUX SURGERY; HIATAL CLOSURE; FUNDOPLICATION; GASTROPLASTY